Ultraviolet‐induced chain extension of poly(ethylene terephthalate) based on radical reaction with the aid of trimethylolpropane triacrylate and glycidyl methacrylate during extrusion. Issue 7 (15th March 2020) - Huang, Wei‐Tao; He, Guang‐Jian; Tang, Wen‐Dong; Cao, Xian‐Wu
Abstract: In order to improve the processing properties of poly(ethylene terephthalate) (PET), carbon–carbon double bonds were end‐capped onto the chain end of PET by reacting with glycidyl methacrylate (GMA) and then the product was reacted with trimethylolpropane triacrylate (TMPTA) based on a free radical reaction initiated by ultraviolet light to form long‐chain branching structures. The reaction was demonstrated by intrinsic viscosity measurements, carboxyl content analysis, Fourier transform infrared spectroscopy and size exclusion chromatography. Then the rheological and thermal properties of PET were investigated with various TMPTA and GMA contents. Chain extended PET displayed higher complex viscosity than pristine PET and pronounced shear‐thinning behavior. Moreover, the relaxation time spectrum revealed that the modified PET displayed a longer relaxation time during the relaxation process, which was attributed to the higher degree of entanglements resulting from long‐chain branching. Besides, its crystallization temperature and melt temperature shifted to lower temperatures, and the glass transition temperature shifted to higher temperature, indicating that the thermal properties of the modified PET had also been improved. Thus this method can be used to improve the overall properties of PET. © 2020 Society of Chemical Industry Abstract : Glycidyl methacrylate (GMA) first reacted with the end groups of poly(ethylene terephthalate) (PET), and then the PET chains with unsaturated bonds reacted with trimethylolpropane triacrylate (TMPTA) initiated by ultraviolet light to form branches.